RISIKO HUKUM PERUSAHAAN MENGABAIKAN LEGALITAS ASURANSI DALAM KEGIATAN BISNIS - Novi Purwaningsih; Retno Catur (UNES Law Review, 2023)
Insurance is a financial instrument that can help communities and companies reduce financial risk due to unexpected events such as natural disasters, accidents or property loss. The use of insurance as a form of financial protection is increasingly important in the face of ever- increasing risks today. In the world of insurance business, the aim is to transfer risk, compensate for losses, cover the welfare of members, transfer risks, raise funds and balance premiums, and provide protection in the event of an incident on company property. on the google scholar database. The legal basis for insurance in Indonesia is stated in Law Number 2 of 1992 concerning Insurance Business (UU UPA). The UPA Law was later amended by Law Number 40 of 2014 concerning Insurance Companies need insurance for various reasons. When conducting business, we are responsible for the well- being of many, from employees to customers. There are several types of insurance risk, including: pure risk, speculative risk, special risk, fundamental risk, individual risk, asset risk and liability risk. There are four things that can be done to manage risk, namely: avoidance. controlling, delaying and diverting. The importance of the company having insurance legality to provide protection when experiencing risks in the future.